Analisis Kemampuan Menulis Teks Proposal pada Siswa Sekolah Dasar 060875 - Aprina Siregar; Martha Traci Simanjuntak; Melina Marbun; Hendra Kurnia Pulungan (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study aims to analyze the ability to write proposal texts for grade VI elementary school students. The ability to write proposals is one of the important skills for students to master, because proposal texts are often used in everyday life and in the world of work. The research method used is descriptive qualitative. Data were obtained through a proposal text writing test to fifth grade students of SD 060875. The results showed that most students still had difficulties in writing proposal texts. These difficulties include formulating the background, objectives, and activity plan. In addition, most students also experienced problems in developing the content of the proposal and using good and correct language. Based on these findings, this study recommends the need for intensive training and guidance for students in writing proposal texts so that their abilities can improve.